2023
DOI: 10.3390/ijms241210122
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Enhances Transepithelial Sodium Transport in the Lung Alveolar Model: Integrating Network Pharmacology and Mechanism Study

Abstract: Luteolin (Lut), a natural flavonoid compound existing in Perilla frutescens (L.) Britton, has been proven to play a protective role in the following biological aspects: inflammatory, viral, oxidant, and tumor-related. Lut can alleviate acute lung injury (ALI), manifested mainly by preventing the accumulation of inflammation-rich edematous fluid, while the protective actions of Lut on transepithelial ion transport in ALI were seldom researched. We found that Lut could improve the lung appearance/pathological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For instance, Okabe et al ( 54 ) found that orthotopic fetal lung tissue direct injection into the lungs of mice showed a preventive effect against PQ-induced ALI. Meanwhile, Chen et al ( 55 ) discovered that luteolin enhances trans-epithelial sodium transport in 3D alveolar epithelial organoid, effectively reducing respiratory symptoms. These studies have fully proven that organoid technology has broad application prospects in the field of personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Okabe et al ( 54 ) found that orthotopic fetal lung tissue direct injection into the lungs of mice showed a preventive effect against PQ-induced ALI. Meanwhile, Chen et al ( 55 ) discovered that luteolin enhances trans-epithelial sodium transport in 3D alveolar epithelial organoid, effectively reducing respiratory symptoms. These studies have fully proven that organoid technology has broad application prospects in the field of personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lut reduced the LPS-induced fatal toxicity and expression of pro-inflammatory factors in mice [ 28 ]. In addition, Lut blocked prostate cancer cell growth and promoted their apoptosis [ 17 ]. Studies have displayed the regulatory effects of Lut on neutrophils [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human alveolar epithelial cells (BEAS-2B) were provided by procell (Wuhan, China) and cultivated in DMEM (Solarbio, Beijing, China) that contained 1% antibiotics and 10% fetal bovine serum (FBS) (Solarbio) under 37 °C with 5% CO 2 . To construct ALI cell model, BEAS-2B cells (1.0 × 10 4 /well) were inoculated in the 96-well plates, followed by 12 h treatment with 10 µg/mL LPS or PBS (Solarbio) [ 17 ]. For drug treatment group, cells were treated with LTE at 10 ug/mL (Xian Musen Bioengineering, Xian, China) or Lut (Solarbio) at 10 µM for 24 h and then stimulated with LPS(10 µg/mL, 12 h) [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable Development Goals (SDGs) [8]. Acute lung injury (ALI) such as COVID-19 induces extensive lung inflammation and finally causes fatal respiratory failure [9]. In addition, chronic-inflammation-induced lung disorders such as interstitial pneumonia gradually damage lung alveoli, and COPD sometimes manifests as a sequela of COVID-19; both of these disorders are becoming major problems [10,11].…”
Section: Introductionmentioning
confidence: 99%